Proceedings of 36th International Cosmic Ray Conference — PoS(ICRC2019) 2019
DOI: 10.22323/1.358.0209
|View full text |Cite
|
Sign up to set email alerts
|

The Issue with Diffusive Shock Acceleration

Abstract: We discuss the recent developments in the theory of diffusive shock acceleration (DSA) by using both first-principle kinetic plasma simulations and analytical theory based on the solution of the convection/diffusion equation. In particular, we show how simulations reveal that the spectra of accelerated particles are significantly steeper than the E −2 predicted by the standard theory of DSA for strong shocks, in agreement with several observational pieces of evidence. We single out which standard assumptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Yet, the degree of hardening or even its very existence were largely questioned over the past decade. This stems mostly from the non-detection of a corresponding signature in radio or gamma-ray observations of young SNRs, with inferred indices for the emitting particle populations of ∼ 2.2 − 3.0 (Caprioli & Haggerty 2019). Additional evidence challenging concave distributions from non-linear DSA came from analyses of locally measured CR spectra in the framework of standard Galactic propagation models (see, e.g., Trotta et al 2011;Evoli et al 2019); despite coming with different assumptions on source and transport terms, they invariably require power-law indices in the range ∼2.3-2.4 for the nuclei injection spectra above ∼10 GeV (although it remains unclear in this context how exactly such injection spectra are shaped by the processes of acceleration in the source and escape from it).…”
Section: Sn 1987amentioning
confidence: 99%
“…Yet, the degree of hardening or even its very existence were largely questioned over the past decade. This stems mostly from the non-detection of a corresponding signature in radio or gamma-ray observations of young SNRs, with inferred indices for the emitting particle populations of ∼ 2.2 − 3.0 (Caprioli & Haggerty 2019). Additional evidence challenging concave distributions from non-linear DSA came from analyses of locally measured CR spectra in the framework of standard Galactic propagation models (see, e.g., Trotta et al 2011;Evoli et al 2019); despite coming with different assumptions on source and transport terms, they invariably require power-law indices in the range ∼2.3-2.4 for the nuclei injection spectra above ∼10 GeV (although it remains unclear in this context how exactly such injection spectra are shaped by the processes of acceleration in the source and escape from it).…”
Section: Sn 1987amentioning
confidence: 99%
“…Recent observations have indicated that CCSNe commonly have CCSM with a size of R w ∼ a few × 10 14 -10 15 cm (Boian & Groh 2020;Chugai & Utrobin 2022;Terreran et al 2022). DSA should operate as in SN remnants, which predicts CR energy fractions of ∼10%-20% and spectral indices of s cr ∼ 2, being supported by numerical simulations (Axford et al 1977;Krymskii 1977;Bell 1978;Blandford & Ostriker 1978;Schure et al 2012;Caprioli & Spitkovsky 2014;Caprioli & Haggerty 2020). This situation is different from high-energy neutrino emission from jets, in which CR acceleration is highly uncertain (Mészáros & Waxman 2001;Murase et al 2006;Murase & Ioka 2013).…”
Section: High-energy Neutrinos From Ccsnementioning
confidence: 84%
“…However, such flat spectra are never observed in SNRs [16,17] or in radio SNe [18], and would be inconsistent with the observed fluxes of Galactic CRs when propagation in the Milky Way is accounted for [19,20]. The reader is referred to [21][22][23] and references therein for more details about the tension between DSA theory and observations, and for the possible solutions that have been suggested in the literature.…”
Section: Introductionmentioning
confidence: 94%